The birth of the talkies from the spirit of music: A genealogy of Tamil film song. Issue 1 (1st October 2016) - Shankar, M.
The emergence of Tamil talkies in the 1930s and 1940s and the enormity of songs in them could be understood only in the context of a number of dynamic factors that conflated each other in the Madras province during the decades. These factors include the widespread popularity of musical dramas in the region as a new popular entertainment form, the introduction of the new mediascape of gramophone and microphones, the changing patterns of patronage that transformed and compelled the classical music practitioners to look into the talkies as an attractive source of income, and the way in which an interface between the popular and the classical had accelerated the process of transformation to each of these segments and compelled them to understand and assimilate the features of the alternative traditions. Along with this, the early Tamil talkies' exposure to the musical styles of different locations in India also contributed to the stabilization of it. This article also looks at why the popular stream emerged strong in this conflation and how the classical traditions that wanted to intervene in the new medium of cinema had been cast aside even as its spirit was effectively assimilated.